Enhanced performance and reprocessability in polypropylene-lignin blends through plasma treatment - Emanuela Bellinetto; Sofia Regoli; Ruggero Barni; Carmen Canevali; Oussama Boumezgane; Luca Zoia; Claudia Riccardi; Stefano Turri; Gianmarco Griffini (Journal of Bioresources and Bioproducts)
In this work, a new compatibilization strategy for polypropylene-lignin blends was presented, which did not rely on the use of solvents or other chemicals. Soda lignin was subjected to plasma treatment in an argon atmosphere employing a gliding-arc-tornado reactor configuration. The effect of this process was evaluated using electron paramagnetic resonance spectroscopy, nuclear magnetic resonance spectroscopy, differential scanning calorimetry, and thermogravimetric analysis, evidencing significant chemical-structural modifications in lignin, including an increased concentration of phenoxy radicals (60%) and depletion of hydroxyl functionalities (35%). Polypropylene-lignin blends incorporating 5% (w/w), 10% (w/w), and 20% (w/w) of either pristine or plasma-treated lignin were then prepared by melt-blending in a twin-screw extruder, and their thermo-mechanical and rheological properties were investigated in detail. As a result of the plasma-induced modifications occurred in lignin, blends incorporating the plasma-treated material exhibited greater thermo-oxidative stability, more favorable viscoelastic response, significantly improved mechanical performance (137% and 294% strain at break for polypropylene (PP) containing 5% (w/w) and 10% (w/w) of treated lignin, respectively), and enhanced thermo-mechanical reprocessability (> 95% retention of yield strength and strain at break after re-extrusion). This work provided the first demonstration of the effectiveness of plasma treatment as a viable and sustainable strategy to improve filler-matrix interactions in polypropylene-lignin blends without the use of solvents, chemical compatibilizers or additional wet-chemistry steps, paving the way for the development of lignin-based thermoplastic polyolefin materials with enhanced thermo-mechanical characteristics and improved reprocessability.